Gerindra Party's Political Campaign Strategy in the General Election on TikTok Social Media: Strategi Kampanye Politik Partai Gerindra Dalam Pemilihan Umum di Media Sosial Tiktok - I Kadek Marssel Bagia Sedana; Dedy Pribadi Uang (Universitas Indo Global Mandiri, 2026)
Purpose : The research aims to analyze how the Gerindra Party employs TikTok to enhance voter engagement, expand political influence, and shape public opinion Design/methodology/approach : This study applies a qualitative approach using literature review and content analysis of the official Gerindra TikTok account. Findings : The findings reveal that Gerindra’s strategy is grounded in three main theories: Uses and Gratifications, Agenda Setting, and Gatekeeping. Through creative content such as the “Joget Gemoy” dance trend and the “Oke Gas Prabowo Gibran Paling Pas” jingle, the party successfully builds a relatable image among younger voters. Furthermore, by setting relevant public issues and engaging directly with users through comment responses and video interactions, Gerindra fosters an effective two-way digital communication. These results indicate that TikTok functions not only as an entertainment medium but also as a strategic platform for political communication and public image building. Practical Implication : Describes how the findings can be applied in practice, for example - their relevance to policymakers, practitioners, or specific sectors. Furthermore, this study can serve as a reference for political parties and communication practitioners in designing effective digital campaigns through creative, interactive content that is adapted to both social media culture and algorithms, with a view to increasing voter engagement and strengthening political image. Originality/value : Emphasizes what makes the research unique, innovative, or valuable. It should highlight the paper’s contribution to the existing body of knowledge or its novel perspective. Paper type : Research Paper